1994
DOI: 10.1136/hrt.71.5.437
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Helicobacter pylori infection and coronary heart disease.

Abstract: Background-There is evidence suggesting that early life experience may influence adult risk of coronary heart disease (CHD). Chronic bacterial infections have been associated with CHD. Objective-To determine whether Helicobacter pylori, a childhood acquired chronic bacterial infection, is associated with an increased risk of coronary heart disease in later life. We used a case-control comparison to investigate whether H pylori infection was associated with adult CHD. We also studied possible associations of Hp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
305
5
14

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 585 publications
(334 citation statements)
references
References 8 publications
10
305
5
14
Order By: Relevance
“…Further, a wealth of clinical evidence has established that H. pylori is causally related to peptic ulcer disease, but is also associated with conditions ranging from intermittent nausea and vomiting to gastric carcinoma/lymphoma and, possibly, ischaemic heart disease (Forman et al 1991;Mendall et al 1994;NIH 1994;Parsonnet et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a wealth of clinical evidence has established that H. pylori is causally related to peptic ulcer disease, but is also associated with conditions ranging from intermittent nausea and vomiting to gastric carcinoma/lymphoma and, possibly, ischaemic heart disease (Forman et al 1991;Mendall et al 1994;NIH 1994;Parsonnet et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…7 Helicobacter pylori (H. pylori) is a common, curved, spiral, Gram-negative bacteria that has been associated with various extradigestive disorders, in addition to its well-known association with gastrointestinal disorders. [8][9][10][11] In the past year, several studies have suggested an association between H. pylori infection and various extradigestive diseases, including cardiovascular and immunological disorders. As the release of large amounts of various proinflammatory and vasoactive substances, such as cytokines, eicosanoids, and acute phase reactant proteins follows gastric colonization by H. pylori, the bacterium may be involved in vascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…< [5]. En 1994, une autre série annonçait une association entre maladie coronaire et infection par Helicobacter pylori [6]. Publiés en 1997, deux essais cliniques pilotes [7,8] ont suggéré qu'un traitement antibiotique par macrolide améliore le pronostic de la maladie coronaire.…”
Section: Historique De L'hypothèse Infectieuseunclassified
“…Il est donc possible de rechercher des associations entre la signature sérolo-gique d'une infection microbienne et l'existence (études cas-témoins) ou la survenue (études prospectives de cohorte) d'une maladie coronaire. Cette méthode a mené à impliquer C. pneumoniae [4] ou H. pylori [6]. Toutefois, l'épidémiologie établit des associations statistiques où le lien de causalité n'est jamais qu'une interprétation parmi d'autres [1].…”
Section: éPidémiologieunclassified